Prognostic evaluation of the impact of restricted horizon visibility on the accuracy of position (coordinates) obtained with GNSS based on empirical data - Oleksandr Yanchuk; Roman Shulgan (Geodesy and Cartography, 2020)
In this research, the practical check of regression equation to calculate the prognostic root mean square error (RMSE) of the final point position of the base line in relation to the initial one has been executed. For the investigation, experimental data from three satellite receivers within two days on 5 points have been used. According to the received results, the regression equation to calculate the RMSE of spatial, planned and height position of the final point of the base line in relation to the initial value has been made. These equations allow executing the prognostic evaluation of accuracy for conducting satellite calculations based on data about available obstacles. The dependencies received for the duration of observations sessions for 1 hour, the vectors with the length of 4 km, and the coefficient value of openness from 5.17 to 10.31 have been presented.